A systematic review of phase II trials exploring anti-PD-1/PD-L1 combinations in patients with solid tumors. (December 2021) - Martorana, F.; Colombo, I.; Treglia, G.; Gillessen, S.; Stathis, A.
Highlights: Recently published phase II trials of anti PD1/PD-L1 combination regimens are heterogeneous. Other immunotherapeutic agents and targeted agents are the more common partners. Trials design is mainly non-randomized, while ORR represents the most used primary endpoint. Across the different studies, ORRs span from 0 to 91% and G ≥ 3 TEAEs go from 0 to 100%. Only a minority of these combinations proceed to phase III and eventually receive approval. Abstract: Background: A high number of combinations of PD-1/PD-L1 inhibitors with other anti-cancer therapies are in clinical development. The usefulness of phase II trials in evaluating their efficacy and safety is unclear. Materials and methods: We performed a systematic search on PubMed and Cochrane Library for phase II trials of PD-1/PD-L1 inhibitors in combination with other anti-cancer therapies (systemic therapy and/or radiotherapy) published between January 1st 2018 and December 31st 2020. Study design, primary endpoint and main outcomes were registered for each paper. Results: 119 articles reporting on 65 regimens were included in our analysis. Backbone agents were more frequently PD-1 inhibitors (pembrolizumab = 47, nivolumab = 41, camrelizumab = 3) followed by anti-PD-L1 (durvalumab = 19, atezolizumab = 6, avelumab = 3). Therapeutic partners were other immunotherapeutic agents (n = 46), targeted therapies (n = 40), chemotherapy (n = 22) or radiotherapy (n = 11). The majority of articles reported on single-arm trials (n = 87, 73%) and response rate was the most frequent primary endpoint (n = 69, 58%). Objective responses, registered in 109 (92%) articles, ranged between 0% and 91%. The incidence of grade 3 or higher treatment-related adverse events, clearly reported in 97 (82%) articles, spanned from 0 to 100%. Five combinations received regulatory approval by Food and Drug Administration or European Medicine Agency for 9 different indications, based on the results of a phase II trial (n = 3) or on a confirmatory phase III trial (n = 6). Conclusions: The landscape of phase II trials evaluating PD-1/PD-L1 inhibitors with other anticancer therapies is heterogeneous. Combinations of two immunotherapeutic agents have been the most investigated. Only a minority of indications (8%) granted regulatory approval.